2006
DOI: 10.1093/jnci/djj394
|View full text |Cite
|
Sign up to set email alerts
|

Female Survivors of Childhood Cancer: Preterm Birth and Low Birth Weight Among Their Children

Abstract: Late effects of treatment for female childhood cancer patients may include restricted fetal growth and early births among their offspring, with risks concentrated among women who receive pelvic irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
218
2
14

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(253 citation statements)
references
References 34 publications
19
218
2
14
Order By: Relevance
“…Recently, a large cohort study of female survivors of childhood cancer found that 19.2% of 337 women with childhood HD had a preterm birth compared with 12.6% among sibling controls (Signorello et al, 2006). Another study reported 11 stillbirths among 729 births of female survivors of childhood HD, corresponding to a relative risk of 1.6 (95% CI: 0.64-4.03) (Green et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large cohort study of female survivors of childhood cancer found that 19.2% of 337 women with childhood HD had a preterm birth compared with 12.6% among sibling controls (Signorello et al, 2006). Another study reported 11 stillbirths among 729 births of female survivors of childhood HD, corresponding to a relative risk of 1.6 (95% CI: 0.64-4.03) (Green et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The CCSS examined pregnancy outcomes in both male and female survivors in comparison with their sibling cohort. 39,40 The offspring of female survivors were more likely to be born before 37 4.0 [95% CI, 1.6-9.8], P ¼ .003). The frequency of premature birth was not found to be increased by previous maternal exposure to increasing doses of chemotherapy with alkylating agents.…”
Section: The Effect Of Radiotherapy On Testicular Functionmentioning
confidence: 99%
“…The included studies were published between 1999 and 2014, and all of them were cohort studies [4,[6][7][8][9][10][11][12][13][14][15][16][17][18]. A total of 10,717 women with radiation therapy and 11,128 women without radiation therapy from 13 studies were evaluated [4, 6-15, 17, 18].…”
Section: Resultsmentioning
confidence: 99%
“…In fertility factors, 5 studies were described about infertility [6,9.12,14, 18], 2 studies were based on AMH values [4,17], 2 studies on AOF [10,16], 3 studies on stillbirth or neonatal death [7,8,13], 2 studies on spontaneous abortion [7,12], 2 studies on congenital anomaly [7,15], 2 studies on low birth weight [7,11] and 1 study on preterm birth [11]. In radiation therapy methods, 4 studies were performed in radiation therapy without specific description [10,12,16,2], 2 studies on abd-pelvic radiation [6,7], 2 studies on ovarian radiation [8,15] and each of the 6 last studies were performed on pelvic radiation [4], abdominal or total body radiation [17], hypothalamic or pituitary radiation [14], nasopharyngeal radium irradiation [9], uterus radiation [11], uterus and ovarian radiation [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation